Organização parlamentar, processo decisório e produção legislativa no cenário político capixaba : uma análise da Assembléia do Estado do Espírito Santo na 16ª legislatura (2007-2010) - Pessine, Karina Melo (2013)
This research is a study of the legislative process and the production of laws in ALES, during the 16th Legislature. The scope of the study was to analyze the impact of the rules contained in the bylaws and the state constitution, the production of laws between 2007 and 2010. The general assumption of the approach comes from the New Intitucionalismo theoretical movement of contemporary science policy, which allows us to infer that the institutional rules, as well as being simple rules for the organization of the Legislative Houses, influence decision making and hence the production of laws . Importing the analysis of distributive, informational and partisan models of legislative organization, the research concluded that the ALES , 2007-2010, kept their production aligned to distributive version. The parliamentary capixaba acted individually in order to maintain their electors. Concerning the work of comissional system, we identified the inability of commissions of the ALES to influence decision-making process. The standing committees have no ability to shape the projects that pass through them. The arrangements for processing directly influences the production of ALES laws, notably the laws written by the Executive, since these laws, were processed, very often, on an emergency basis. About the parties, party fragmentation identified in ALES ends up reflecting on data obtained on the production of laws, to the extent that there is no real coordination around the parties as key actors in the legislative process of ALES. Anyway, in brief summary, there has been the imposition of the agenda by the Executive. The approved projects, important themes and statewide, were mostly proposed by the Executive, the urgency impacts executive bills that are approved in short time; commissions not have minimal influence on power projects by the Executive, and the parties, highly fragmented, aren’t instance with joint capacity.